Pemanfaatan Produk Ramah Lingkungan Bagi Mahasiswa : Implemen-tasi Minat Beli - Serly Charita Harahap; Dahliyanti Dahliyanti; Fadya Nabila; Romi Aldiansyah; Sari Wulandari (Jurnal Ekonomi, Manajemen Pariwisata dan Perhotelan, 2025)
Environmental issues, particularly waste management, have become critical problems that demand attention from all societal levels, including university students as agents of change. This study aims to analyze the influence of environmental knowledge and word of mouth on environmental attitudes and the purchase intention of eco-friendly products among students. A qualitative descriptive method was employed, using semi-structured interviews with five students from various study programs at the State Islamic University of North Sumatra (UINSU). The findings indicate that students possess a good understanding of eco-friendly products and have begun incorporating them into their daily lives, despite challenges such as higher prices, limited access, and insufficient education. Factors such as social media, personal experiences, and the influence of campus figures play a significant role in shaping their purchase intentions. Most respondents also expressed a willingness to pay more for products that offer long-term quality and positive environmental impact. This study highlights the importance of institutional support in fostering sustainable lifestyles through facilities and programs that encourage environmentally responsible consumption.